Czech psychology students' attitudes towards same-sex parenting. Issue 3 (2nd July 2020) - Tušl, Martin; Gato, Jorge; Tasker, Fiona; Figueroa, Victor
ABSTRACT: Czech society has been increasingly more liberal toward LGBTI individuals and their parenting rights, although the Czech legislative system still does not treat same-sex couples equally to heterosexual couples. Attitudes of professionals who work with children and families are particularly important, as prejudice might be harmful in these circumstances. The present study aimed to evaluate the attitudes of future psychologists, participants were 164 psychology students from a university in Prague, the Czech Republic. They were presented with a vignette depicting a situation of a couple in a restaurant with their 4-year-old son who gets upset during the meal. The vignette was followed by a set of Likert scale items evaluating the parents' and the child's behaviour. Participants were randomly assigned to one of the eight versions of the vignette varying by the way how the couple solved the situation, the sexual orientation of the parents, and the gender of the acting parent. Overall, the couples were rated more favourably in the positive parenting situation than in the negative, and participants evaluated gay and lesbian parents more favourably than heterosexual parents. Results are discussed taking into account specific sample characteristics and the social climate regarding LGBTI rights in the Czech society.